RE-MAPPING ENGINE CONTROL UNIT (ECU) UNTUK MENAIKKAN UNJUK KERJA MESIN SEPEDA MOTOR - Muji Setiyo; Leo Utoro (SINTEK JURNAL: Jurnal Ilmiah Teknik Mesin, 2017)
Motorcycles for competitive purposes require a proper adjustment of ignition to produce the most optimum performance. For this reason, this article presents one of re-mapping technique on the Stand Alone Electronic Control Unit (ECU) applied to 130 cc motorcycle injection for competition purposes. This re-mapping activity aims to produce the best torque and power output. The method used by combining four fuel mappings and two ignition mappings tested with the full factorial design. The results showed that lean combustion and advanced ignition timing were able to produce the optimum torque of 11.57 Nm and optimum power of 19.6 hp.